Tipologi Tafsir Ekonomi terhadap Cryptocurrency Berbasis Stabilitas Nilai: Komparasi Bitcoin dan Stablecoin sebagai Alat Tukar dalam Kerangka Maqashid Syariah (Hifdz al-Mal) - Mush’ab , Muhammad (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The rise of cryptocurrency raises a fundamental issue in Islamic economics: can decentralized digital assets perform the functions of money (naqd) and a medium of exchange (tsaman) as required by Islamic law? Most previous studies treat cryptocurrency as a single, uniform category, thus failing to capture the fundamental differences between highly volatile assets such as Bitcoin and highly stable assets such as stablecoins. This study aims to develop a typology of economic interpretations of cryptocurrency based on the level of value stability to test its suitability as a medium of exchange within the framework of Islamic law (maqashid), specifically hifdz al-mal. The study uses a library research method with a qualitative-comparative approach that integrates maqashid (money), maudhu'i (thematic) interpretations, and contemporary contextual interpretations of Q.S. An-Nisa [4]: ​​29 and Q.S. At-Taubah [9]: 34. The analysis is framed by the theory of money in Islam (Al-Ghazali, Ibn Taymiyyah, Al-Maqrizi, Chapra) and tested with empirical data on the price behavior of Bitcoin and stablecoins. The results of the study show three findings. First, Bitcoin's extreme volatility creates gharar fahisy which destroys the certainty of value in transactions so that Bitcoin does not fulfill the functional requirements as a medium of exchange according to the maqashid interpretation, although it can play a limited role as a long-term store of value. Second, fiat-based stablecoins (USDT and USDC) are closer to the tsaman function because their value stability reduces gharar, but have not fully realized hifdz al-mal due to reserve risks, issuer governance, and the lack of authority legitimacy. Third, value stability is a necessary but not sufficient condition for an asset to have money status in Islam, because the dimension of ulil amri (issuance and guarantee authority) is constitutive. This research confirms that the Sharia assessment of digital currency must shift from generic condemnation to functional classification based on value stability and governance, while also offering a framework for the development of a Sharia-compliant digital economy oriented toward the welfare of the community.